Death by jury: group dynamics and capital sentencing - Connell, Nadine M. (Criminal justice: recent scholarship, 2009)
The death penalty and discretion in America -- The role of the jury -- Understanding groups in context -- Measuring groups with the capital jury project -- Testing group dynamics -- What juries do : putting it all together